Women and the state in modern Indonesia - Blackburn, Susan, 1947- (Cambridge University Press, 2004)
In the first study of the kind, Susan Blackburn examines how Indonesian women have engaged with the state since they began to organise a century ago. Voices from the women's movement resound in these pages, posing demands such as education for girls and reform of marriage laws. The state, for its part, is shown attempting to control women. The book investigates the outcomes of these mutual claims, and the power of the state and the women's movement in improving women's lives. It also questions the effects on women of recent changes to the state, such as Indonesia's transition to democracy and the election of its first female president. The wider context is important. On some issues, like reproductive health, international institutions have been influential, and as the largest Islamic society in the world, Indonesia offers special insights into the role of religion in shaping relations between women and the state.--Publisher description.